ON SUN-DRYING OF BOMBAY DUCK - PRABHU, P V (Fishery Technology, 2025)
Sun-drying of Bombay duck by hanging on scaffolds gavebetter products than those obtained by drying them in trays. Optimumrate of drying and quality of dried product were obtained whenthe fish were suspended at the rate of 50 to 60 per meter lengthof the rope. The quality of the raw material as affected by thedelays in different hauls in the fishing trip was reflected in thedried products also.